Government Expenditure according to Functions and Economic Growth in Indonesia - Irwan Suriadi; Siti Sriningsih; Siti Fatimah (PT FORMOSA CENDEKIA GLOBAL, 2023)
The purpose of this study is (1) To analyze the causal relationship of government spending based on functions with economic Growth in Indonesia and (2) To analyze the impact of government spending based on functions on economic growth. The data used in this study is panel data for all provinces in Indonesia from 2005 – 2020. The data collection technique used is a documentation technique, with all data collected being secondary data. These data were obtained from the Central Bureau of Statistics (BPS), Ministry of Finance. Research results show that variable financial spending has a positive relationship between Economic Growth, variable government spending the Education function has a positive relationship between Economic Growth and government spending on the Education function, Variable government spending on housing and public facilities has a positive relationship between Economic Growth, variable government spending on housing and public facilities has a positive relationship between government spending on housing and public facilities with Economic Growth, variable spending government economic function has a positive relationship between Economic Growth and government spending the Economic function, Variable government spending the tourism function and culture has a positive relationship between Economic Growth, variable government spending public service function has a positive relationship between government spending public service function with Economic Growth , variable government spending function order and security has a positive relationship between Economic Growth.